2010
DOI: 10.1590/s1516-14392010000200024
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bioactive materials used on the dentin surface whitened with carbamide peroxide 16%

Abstract: This study investigated the influence of bioactive materials on the dentin surface whitened. Material and Methods: Three bovine teeth were shaped into three dentin wafers. Each wafer was then sectioned, into six dentin slices. One slice from each tooth was distributed into one of 6 groups: 1.CG = control group (distilled water); 2.WT = whitening treatment; 3.WT + MI Paste Plus, applied once a day; 4.WT + Relief ACP30, applied once a day for 30 mintes; 5.WT + Relief ACP60, applied once a day for 60 minutes; 6.W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
22

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 24 publications
0
27
0
22
Order By: Relevance
“…Another in vitro study investigated the in situ influence of Biosilicate on whitened enamel and dentin surfaces using the Knoop hardness test. The results indicated that the biomaterial benefited the tooth hardness and morphology, preventing demineralization (11).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Another in vitro study investigated the in situ influence of Biosilicate on whitened enamel and dentin surfaces using the Knoop hardness test. The results indicated that the biomaterial benefited the tooth hardness and morphology, preventing demineralization (11).…”
Section: Discussionmentioning
confidence: 97%
“…In response to these comments, the optimization of the usual methods of dental caries prevention and the development of new strategies are of fundamental importance for the promotion of oral health (12,13). In this context, bioactive materials such as bioglass have been used as remineralizing and desensitizing agents, but there are few studies describing these materials (11)(12)(13). Further research led to the development of Biosilicate, a new fully crystalline glass ceramic.…”
Section: Introductionmentioning
confidence: 99%
“…Embora essa sensibilidade seja transitória -cessando gradualmente após o término do tratamento -ela pode ser extremamente desconfortável para alguns pacientes, principalmente para aqueles que já apresentam quadro de dentes sensíveis. Nesse sentido, Pinheiro et al 68 propuseram um estudo in vitro para avaliar a influência de diferentes materiais bioativos combinados com peró-xido de carbamida 16% (agente clareador) sob a estrutura da dentina. Pelos resultados obtidos, os autores demonstraram que a utilização do agente clareador em conjunto com alguns dos materiais bioativos testados, incluindo o Biosilicato ® , contribuiu efetivamente para a remineralização da estrutura dentária no decorrer dos experimentos, o que, possivelmente, promoveria a diminuição da sensibilidade originada durante e/ou após o tratamento de clareamento.…”
Section: Biosilicatounclassified
“…45,46,[64][65][66][67][68][69][70][71][72][73][74] Ainda convém mencionar estudos relativos ao seu processamento a partir de diferentes rotas de síntese, 49,75 bem como à sua conformação para a obtenção de matrizes macroporosas com potencial uso na engenharia de tecidos (scaffolds). 76 Integrada ao Programa de Estímulo à Interação UniversidadeEmpresa para Apoio à Inovação, a Vitrovita, empresa que detém o licenciamento das patentes do Biosilicato ® , foi coexecutora do projeto "Rede multidisciplinar de pesquisa em biosilicatos para aplicação na saúde humana", financiado pelo CNPq (Fundo Verde Amarelo -FVA/ CNPq).…”
unclassified
“…Pesquisas têm mostrado que os agentes clareadores podem causar alterações no conteúdo mineral dos dentes [1] , resultado da desmineralização do esmalte e da dentina e, como consequência, gerar efeitos indesejáveis à estrutura dental, como aumento da rugosidade [2][3][4] , diminuição da dureza [5][6][7] e alteração da morfologia superficial [7][8][9] .…”
Section: Introductionunclassified